Nepenthes diversity in Sulasih Talang Nature Reserve - West Sumatra - DWI MURTI PUSPITANINGTYAS; HARY WAWANGNINGRUM (Biodiversitas Journal of Biological Diversity, 2007)
Nepenthes is one of carnivorous plants which very popular as ornamental plant. Most of them grow in mountain forest habitat above 1.000 m a.s.l. Sumatra has the richest Nepenthes flora after Borneo, with 29 species. The observation was done in Sulasih Talang Nature Reserve - West Sumatra. According to this inventory in Sulasih Talang Nature Reserve, there are 6 species can be found in this area, which 5 species are endemic to Sumatra, that are N. pectinata, N. inermis, N. bongso, N. spathulata and N. talangensis. N. gracilis is widespread in Sumatra, Borneo and Celebes, whereas the other species N. talangensis is only found in Mount Talang. Threat to those species are, habitat destruction, over exploitation and volcano eruption.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKeywords: Nepenthes, diversity, Sulasih Talang Nature Reserve